2016
DOI: 10.1007/s11892-016-0796-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care Disparities Among Adults with Type 2 Diabetes in the USA

Abstract: Suboptimal glycemic control is more common among Non-Hispanic Blacks (NHBs) and Hispanics than non-Hispanic Whites (NHWs). Disparities in the performance of self-care behaviors may contribute to this. To synthesize knowledge on current self-care disparities, we reviewed studies from January 2011-March 2016 that included NHWs, NHBs, and Hispanics with type 2 diabetes in the United States. Self-care behaviors included diet, exercise, medications, self-monitoring of blood glucose (SMBG), self-foot exams, and not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 77 publications
2
34
0
Order By: Relevance
“…14,15 Quality of diabetes care and preventive care practices to forestall diabetes-related complications vary according to disparities in access to care. 16 For example, even among insured populations, Latinos are less likely to receive regular care and less likely to meet HbA1c targets. 17,18 Lack of access to care in non-Hispanic Blacks is associated with not meeting blood pressure targets.…”
Section: Epidemiologic Overviewmentioning
confidence: 99%
“…14,15 Quality of diabetes care and preventive care practices to forestall diabetes-related complications vary according to disparities in access to care. 16 For example, even among insured populations, Latinos are less likely to receive regular care and less likely to meet HbA1c targets. 17,18 Lack of access to care in non-Hispanic Blacks is associated with not meeting blood pressure targets.…”
Section: Epidemiologic Overviewmentioning
confidence: 99%
“…Recent studies estimate 1 in 3 patients do not take their diabetes medication as prescribed [1, 2], with even higher rates of nonadherence among racial/ethnic minorities [2, 3] and people with low socioeconomic status (SES) [4, 5]. Medication nonadherence is a very costly issue [6], associated with suboptimal glycemic control [7], severe health complications including stroke and heart attack [8], and mortality [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the association may be divergence among various types of coping resources. One review showed that self-care activities were associated with improved glycemic control (21). A previous meta-analysis has proven that social support is not an important risk factor for type 2 diabetes (17).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these work-related psychosocial factors, psychosocial resources, such as social support (20), self-care (21), and social network (22), have been shown to be associated with type 2 diabetes. The effect of workplace psychosocial factors on diabetes may be influenced by coping resources.…”
mentioning
confidence: 99%